Standardization of the Silesian Language: The Current Status and Prospects for Development - Jaroszewicz, Henryk (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
At the beginning of the 20th century, a discussion on the status of the Silesian ethnolect emerged in Poland. Several years ago, the creative and language activist circles advocating for the linguistic autonomy of Silesian initiated actions aimed at the description and codification of the Silesian language. Among the many published works, only the few-page Wstępne zasady pisowni śląskiej (Preliminary Rules of Silesian Orthography) from 2009 and Gōrnoślōnski ślabikŏrz from 2010 can be considered valuable studies that had a real impact on the development of Silesian literature in the second decade of the 20th century. The relatively general normative decisions presented in these works are revised and extensively expanded in Zasady pisowni języka śląskiego (Rules of Silesian Language Orthography) from 2022. This monograph, which codifies not only Silesian orthography but also elements of grammar and vocabulary, can serve as a foundation for further activities towards the complete standardisation of the Silesian language.